Car rental using mobile application development - Mah, Guo Xiang (2025)
This project aims to develop an innovative mobile car rental system that focuses on modernizing the traditional car rental process by integrating real-time tracking features, comprehensive customer support, and an intuitive user interface (UI). The transformation brought by mobile technology to the car rental industry has completely changed the way users interact with rental services. By analyzing existing car rental mobile applications such as GoCar Malaysia, TREVO, and Moovby, this study identifies strengths and weaknesses to inform the development of the proposed system. To address the problems found in these existing systems, the project objectives for the proposed system are discussed. The advantages of the existing systems have been adopted and integrated into the proposed system to enhance its functionality. In the proposed car rental mobile application system, it provides the modules included profile module, booking module, history module, and tracking module. The project uses the Android Studio and Flutter programming languages to develop a mobile-based car rental mobile application system. The choice of a mobile application is driven by the fact that nearly everyone uses mobile devices and to transform the traditional car rental booking process into a modern, more convenient experience. Through this project, our goal is to transform the car rental experience and provide users with a seamless, efficient, and modern rental service platform. This effort not only solves current industry challenges but also sets new standards for convenience, reliability, and customer satisfaction in the car rental sector.